Unraveling the Complexities of Polycystic Ovarian Syndrome: A Comprehensive Review - Archana Kumari; Satya Narayan jha (Talenta Publisher, 2024)
Background: Polycystic Ovarian Syndrome (PCOS) is a complex endocrine disorder affecting reproductive-age women, characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. Objective: The aimed was to explore the key topics including the role of insulin resistance and hyperinsulinemia in PCOS pathogenesis, the impact of hormonal imbalances on menstrual irregularities and fertility, and the association of PCOS with metabolic syndrome and cardiovascular risk factors. Methods: This comprehensive review delves into the multifaceted nature of PCOS, exploring its etiology, pathophysiology, clinical manifestations, diagnostic criteria, and management strategies. Results: The review discusses current diagnostic criteria and controversies surrounding PCOS diagnosis, as well as evidence-based approaches to treatment, encompassing lifestyle modifications, pharmacological interventions, and assisted reproductive technologies. Conclusion: By synthesizing current knowledge and emerging research findings, this review aims to provide a comprehensive overview of PCOS for clinicians, researchers, and individuals affected by this prevalent endocrine disorder.